Темпоральні характеристики володіння чужим майном - Гуйван, Петро Дмитрович; Гуйван, П. Д.; Guyvan, Petro (ВД "Гельветика", 2020)
Ця наукова праця присвячена дослідженню актуального питання стосовно правових підстав та результативності нетитульного володіння як належного юридичного явища та оформлення суспільно очікуваного результату – пожвавлення матеріального обороту як елементу побудови ринкового суспільства. Проаналізовано різні аспекти сутності повноважень незаконного фактичного володільця. Визначено правове становище володільця, коли передача майна передбачена договором, але такого виконання не відбувається, з’ясовано можливість застосування до подібних випадків правового режиму утримання чужої речі. Запропоновані істотні зміни до чинного українського законодавства, які виключають змішування речових та зобов’язальних механізмів регулювання відносин щодо нетитульного утримання чужого майна. В роботі зроблено висновок про наявність у сучасному українському цивільному законодавстві правової підстави для нетитульного володіння чужою річчю, яке потребує подальшого унормування.

The given scientific work is devoted to the research of the actual question concerning the legal grounds and the effectiveness of non-titular possession, as a proper legal phenomenon, and the design of the socially expected result – the revitalization of material turnover as an element of building a market society. Different aspects of the essence of the powers of the unlawful actual owner are analyzed. The legal position of the owner is determined, when the transfer of property is stipulated by the contract, but such fulfillment does not take place, the possibility of applying the legal regime of detention of another’s property to such cases is clarified. Substantial changes to the current Ukrainian legislation are proposed, which exclude the mixing of material and binding mechanisms for regulating relations regarding the non-titular maintenance of another’s property. The article investigates the content of the concept of illegal possession as a phenomenon that characterizes the possession of a thing by a person who illegally seized it from the owner or title holder, or otherwise acquired, without having proper grounds for this acquisition. The criteria for the division of such ownership into good faith and bad faith are defined. A specific interpretation of these legal definitions is provided. The author’s position on the necessity of narrowing the doctrinal definition of an unscrupulous illegal owner is substantiated. It should not extend to cases where the acquirer first legally obtained the property (for example, by deed), but then the specified grounds ceased and it was not returned, and cover only a circle of purely material relations, such as theft or other seizure of property out of will. the owner. In other words, when the legal protection of the infringed property is possible in material ways, such as vindication. The article also analyzes the issue of determining the title of property belonging to one person but located in another. Such an analysis identifies a key problem: whether such possession is subject to legal protection, and if so, at what point, in what manner and on what grounds it should occur. The paper concludes that there is a legal basis in modern Ukrainian civil law for non-titular possession of someone else’s thing that needs further regulation.
Гуйван П. Д. Темпоральні характеристики володіння чужим майном / П. Д. Гуйван // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 5-10.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; незаконне володіння чужою річчю; добросовісний набувач; illegal possession of someone else’s thing; conscientious purchaser